LAST MULTIPLIERS FOR η-RICCI SOLITONS - Blaga, Adara M. (Matematichki Bilten, 2018)
Last multipliers are determined for the \(η\)-Ricci soliton tensor. In the particular case of a perfect fluid spacetime, if the potential vector field of the \(η\)-Ricci soliton is of gradient type, we obtain the differential equation satisfied by the last multiplier.